Early Childhood Exposure to Blue Screen and its Association with the incidence of Autism Spectrum Disorder in children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Everyone's life was significantly impacted by blue screens, but kids were especially affected. These days, digital technology has permanently changed our way of life and our emotional and physical well-being. Modern technologies are causing an increasing number of negative effects on "hyper-connected" users, particularly in young children who are screen hooked. This paper aimed to assess clinical outcomes related to the impact of exposure on blue screens on children during early childhood, and it is associated with the prevalence of autism spectrum disorder in children.For this cross-sectional study, clinical data were recorded for 170 children with autism spectrum disorder (ASD), collected from private clinics during a period spanning October 2024 to October 2025. Based on patient age, the study divided the medical records of the pediatric patients into two groups: the first group included 90 younger children aged one to three years, while the second group included 80 older children aged three to ten years. Based on a questionnaire, our study aimed to investigate the extent of children's deep exposure to blue screens and their association with ASD during a one-year follow-up period. This study assessed patients' quality of life using the Childhood Autism Rating Scale (CARS), the Developmental Quotient (DQ), and the Child-Parent Centered Interaction Scale (CPCIS).According to clinical outcomes, a total of 170 children were enrolled in this study. Also, it found that television was almost common screen type used with 50 (55.6%) in the young children group and 35 (43.8%) in the older children group. Based on the related QoL questionnaire, we found lower scores of QoL at children with ages 1 – 3 years in comparison with children with ages 4 – 10 years. Autism severity (CARS) had 38.5 (5.2), developmental quotient (GDS DQ) had 72.1 (12.4), and social interaction (CPCIS) had 18.3 (4.1) in the younger group of children. An older group of children enrolled improvement over than young group, where autism severity (CARS) had 35.2 (4.8), developmental quotient (GDS DQ) had 78.5 (11.6), and social interaction (CPCIS) had 21.5 (3.9).In conclusion, our study showed that excessive screen use can have negative effects on children's mental and physical health. As a result, younger children, ages 1–3 years, were more likely to experience negative outcomes with autism spectrum disorder than children aged 4-10 years.